CMC-coated Fe3O4nanoparticles as new MRI probes for hepatocellular carcinoma - Sudarat Sitthichai (2018)
© 2015 Elsevier B.V. All rights reserved. Pure Fe 3 O 4 nanoparticles and Fe 3 O 4 magnetic nanoparticles (MNPs) coated with carboxymethyl cellulose (CMC) were successfully prepared by co-precipitating of FeCl 2 ·4H 2 O and FeCl 3 ·6H 2 O in the solutions containing ammonia at 80 °C for 3 h. Phase, morphology, particle-sized distribution, surface chemistry, and weight loss were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) including high-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED), thermogravimetric analysis (TGA), and Fourier transform infrared (FTIR) spectroscopy. In this research, CMC-coated Fe 3 O 4 MNPs consisting of Fe 2+ and Fe 3+ ions with 543.3-mM -1 s -1 high relaxivity were detected and were able to be used for magnetic resonance imaging (MRI) application with very good contrast for targeting hepatocellular carcinoma (HCC) without any further vectorization.